Ginsenoside Rd Ameliorates High Fat Diet‐Induced Obesity by Enhancing Adaptive Thermogenesis in a cAMP‐Dependent Manner. Issue 4 (6th March 2020) - Yao, Lu; Han, Zaiqi; Zhao, Guoyan; Xiao, Yanfang; Zhou, Xuenan; Dai, Rongzheng; Han, Meijing; Wang, Zilin; Xin, Rongshuang; Wang, Shuran
Abstract : Objective: With the discovery of thermogenic adipocytes in humans, it has been hypothesized that enhancing adaptive thermogenesis may improve obesity. Although many studies have found that ginseng can improve obesity, the beneficial effects of ginsenoside Rd on obesity and its mechanisms have not been studied. Methods: High‐fat diet‐induced obese mice were used as the study subjects, with intraperitoneal injection of Rd daily at a dose of 15 mg/kg. Body weight and energy metabolism were observed. The effects of Rd on glucose tolerance, insulin sensitivity, and cold tolerance were tested. The expression of genes associated with thermogenesis was analyzed. Finally, the mechanisms by which Rd regulates adaptive thermogenesis were studied. Results: Rd ameliorated obesity and insulin resistance. Rd increased cold tolerance through enhancing thermogenic gene expression in brown adipose tissue and increased the browning of white adipose tissue induced by cold stress. Rd increased intracellular cyclic adenosine monophosphate (cAMP) content. Decreasing intracellular cAMP levels by an inhibitor of adenylyl cyclase SQ22536 abolished the promoting effects of Rd on the expression of thermogenic genes. Conclusions: Rd improves obesity and insulin resistance. The upregulation of thermogenesis by Rd is dependent on the cAMP/protein kinase A signaling pathway.